Novel scFv against Notch Ligand JAG1 Suitable for Development of Cell Therapies toward JAG1-Positive Tumors - Silva, Gabriela (2023)
Funding Information: This research was funded by the Fundação para a Ciência e Tecnologia/Ministério da Ciência, Tecnologia e Ensino Superior (FCT/MCTES, Portugal) grant PTDC/BBB-BMD/4497/2014 (to A.B.), through national funds to iNOVA4Health (UIDB/04462/2020 and UIDP/04462/2020), and the Associate Laboratory LS4FUTURE (LA/P/0087/2020). Publisher Copyright: © 2023 by the authors.